Keselarasan Nilai Kepemimpinan Lokal dan Nasional: Studi Perbandingan Antara Ninik Mamak dan Ki Hadjar Dewantara - Eviana Liswardani Ayu (EKONOMI DAN BISNIS DIGITAL, 2025)
This article aims to examine and compare the leadership values embodied by Ninik Mamak, the traditional leaders of the Minangkabau community, and Ki Hadjar Dewantara, a national figure in Indonesian education. Through a literature review and analysis of academic research, this study explores the fundamental similarities and differences in the principles, ethics, and leadership practices upheld by these two figures within their respective social and cultural contexts. The findings reveal that both Ninik Mamak and Ki Hadjar Dewantara emphasize morally grounded leadership, social responsibility, and leading by example. Ninik Mamak’s leadership is rooted in the customary principle of "adat basandi syarak, syarak basandi Kitabullah", which reflects a balance between local wisdom and Islamic spiritual values. In contrast, Ki Hadjar Dewantara formulated a leadership philosophy expressed in the famous motto: "Ing ngarsa sung tuladha, ing madya mangun karsa, tut wuri handayani", highlighting the leader’s role as a role model at the front, a facilitator in the middle, and a motivator at the back. This comparison illustrates a harmonious alignment of values between local and national leadership models, which can be seen as complementary rather than contradictory. Integrating these values is essential to strengthening leadership character in Indonesia, particularly in shaping leaders who are culturally grounded yet relevant to modern societal challenges. Both figures demonstrate that ideal leadership is not solely based on structural authority, but rather on the ability to guide, nurture, and foster moral and cultural values within society. In Indonesia’s pluralistic context, the harmony between local and national leadership values offers a solid foundation for developing leadership rooted in cultural identity while remaining responsive to global challenges.